2021
DOI: 10.1007/s11033-021-07003-7
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of haloperidol-induced orofacial dyskinesia and neuroinflammation by isoflavones

Abstract: Schizophrenia is a serious mental illness, and its pharmacological treatment consists in the administration of antipsychotics, such as haloperidol. However, treatment with haloperidol often causes extrapyramidal motor disorders such as tardive dyskinesia (TD). TD is a movement disorder characterized by involuntary movements, which can be studied in animals. So far, there is no effective treatment for TD and alternatives have been sought. Thus, the objective was to evaluate the possible protective effect of iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…Our previous study has reported that in both cultured astrocytes and the rat prefrontal cortex, olanzapine increased the expression of IL-1β ( Li et al, 2021c ). Haloperidol increased IL-β in the rat brain ( Sonego et al, 2021 ; Mezzomo et al, 2022 ). These findings suggest that antipsychotics such as olanzapine and haloperidol might significantly affect the NLRP3/caspase-1 signaling, leading to IL-1β production and astrocyte death.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has reported that in both cultured astrocytes and the rat prefrontal cortex, olanzapine increased the expression of IL-1β ( Li et al, 2021c ). Haloperidol increased IL-β in the rat brain ( Sonego et al, 2021 ; Mezzomo et al, 2022 ). These findings suggest that antipsychotics such as olanzapine and haloperidol might significantly affect the NLRP3/caspase-1 signaling, leading to IL-1β production and astrocyte death.…”
Section: Introductionmentioning
confidence: 99%
“…EMPA is an antidiabetic drug that inhibits SGLT2, which offers clinically meaningful protection in type 2 diabetic individuals [ 25 ]. Attenuation of oxidative stress, inflammation, and apoptosis are considered some of the postulated mechanisms of EMPA effects in tissue protection [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased (in comparison to control animals who were only exposed to the vehiculum used) striatal levels of IL-1β were invariably found in rodent models of haloperidol-induced orofacial dyskinesia ( Grover et al, 2013 ; Peroza et al, 2016 ; Thakur et al, 2015 ; Datta et al, 2016 ; Sonego et al, 2018 , 2021 ; Mezzomo et al, 2022 ). Both dyskinesia and IL-1β levels were reduced when the animals received concurrent antioxidant treatment.…”
Section: Biomarkers For Neuroinflammation and Tardive Dyskinesiamentioning
confidence: 99%